ANALISIS PERHITUNGAN DAN PEMOTONGAN PAJAK PENGHASILAN PASAL 21 PADA KARYAWAN TETAP PT. AIR MANADO - Latif, Risna; Sabijono, Harijanto; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Income Tax Article 21, or commonly referred to Article 21 Income Tax is as tax on incomce in the form of wages, salary, honoraria, allowances and other payments to the name and in any form in connection with employment or occupation, services and activities that carried out by private persons subject to tax in the country. the purpose of this research is to analyse whether the application of calculation and deduction of Article 21 income tax at PT. Air in Manado has already met the rule of taxing. The method used in this research is descriptive analysis method, object study was conducted at the PT. Air Manado. Based on thediscussion of research results, it was concluded that in determining the calculation and deduction of Article 21 Income Tax at PT. Air Manado is still not in accordance with the latest tax regulations.Keywords : Article 21 Income Tax